Restricted effects of androgens on glucocorticoid signaling in the mouse prefrontal cortex and midbrain - Amaya, Jorge Miguel; Sips, Hetty C. M.; Viho, Eva M. G.; Kroon, Jan; Meijer, Onno C. (Frontiers in Endocrinology, 2024)
Glucocorticoids are key executors of the physiological response to stress. Previous studies in mice showed that the androgen receptor (AR) influenced the transcriptional outcome of glucocorticoid treatment in white and brown adipocytes and in the liver. In the brain, we observed that chronic hypercorticism induced changes in gene expression that tended to be more pronounced in male mice. In the present study, we investigated if glucocorticoid signaling in the brain could be modulated by androgen. After chronic treatment with corticosterone, dihydrotestosterone, a combination of both, and corticosterone in combination with the AR antagonist enzalutamide, we compared the expression of glucocorticoid receptor (NR3C1, also abbreviated GR) target genes in brain regions where AR and GR are co-expressed, namely: prefrontal cortex, hypothalamus, hippocampus, ventral tegmental area and substantia nigra. We observed that androgen affected glucocorticoid signaling only in the prefrontal cortex and the substantia nigra. Dihydrotestosterone and corticosterone independently and inversely regulated expression of Sgk1 and Tsc22d3 in prefrontal cortex. AR antagonism with enzalutamide attenuated corticosterone-induced expression of Fkbp5 in the prefrontal cortex and of Fkbp5 and Sgk1 in the substantia nigra. Additionally, in the substantia nigra, AR antagonism increased expression of Th and Slc18a1, two genes coding for key components of the dopaminergic system. Our data indicate that androgen influence over glucocorticoid stimulation in the brain is not a dominant phenomenon in the context of high corticosterone levels, but can occur in the prefrontal cortex and substantia nigra.